Antibacterial, antifungal and phytoalexins induction activities of hydrolates of medicinal plants - Franzener, Gilmar; Martinez-Franzener, Alexandra da Silva; Stangarlin, José Renato; Czepak, Márcio Paulo; Schwan-Estrada, Kátia Regina Freitas; Cruz, Maria Eugênia Silva (Semina: Ciências Agrárias, 2007)
The aim of this work was to evaluate the antifungical, antibacterial and phytoalexins elicitors activities of hydrolates, for using in the alternative control of plant diseases. The hydrolates of Helietta apiculata (HA), Conyza canadensis (CC) and Cymbopogon nardus (CN) were used in the concentrations of 1, 5, 10, 15, 20 and 25%. In the phytoalexins assay, sorghum etiolated mesocotyls were used. The antibacterial effect was evaluated on the growth of the bacterium Xanthomonas campestris pv. campestris in liquid nutrient medium and antibiotic (oxytetraciclin 22.5 mg/L + streptomycin 225 mg/L) was used as control treatment. The antifungical effect was evaluated on the micelial growth, esporulation, conidia germination and development of germinative tubes of Alternaria brassicae. The fungicide azoxystrobin (0.08 g a.i./ L) was used as control treatment. There was increment in the phytoalexins synthesis with the increase in hydrolates concentration. The better result was obtained with CN that promoted increase 4.3 times larger in relation to the value of the control treatment with water, followed by HA (2.5 times) and CC (2.1 times). Similar results were obtained to the antibacterial activity with the following inhibition results (%) in the development of the bacterium: CN: 29.8, HA: 14.9, CC: 14.6 and antibiotic: 97.7. The main antifungical effect was observed on the development of the germinative tubes. Hydrolates of CC and HA showed inhibition of up to 69.2 and 56.2%, respectively, being similar to the fungicide azoxystrobin. The hydrolate of CN did not show antifungical effect. These results indicate the presence of phytoalexins elicitors, and antibacterial and antifungical compounds in those hydrolates, however in low concentrations.